Nos 190 anos do nascimento de Sebastião Philippes Martins Estácio da Veiga (1828-1891) - Cardoso, João Luís (2018)
The life, personal and scientific life of Sebastião Philippes Martins Estácio da Veiga, whose 190 years of his birth are celebrated in 2018, is summarily presented. He was born in the Algarve and was commissioned in 1877 by the Portuguese Government to prepare the Carta Arqueológica do Algarve. Of the fieldwork he conducted with remarkable dedication and commitment throughout the then-designated Algarve Province, resulted in the publication of the most brilliant work of Archeology to date produced in Portugal: the Antiguidades Monumentais do Algarve.